Analysis of Research Status for Ubiquitous Power Internet of Things - Bai XIAO; Wenkai ZHOU; Zhuo JIANG; Xuesong QI; Xiangzhi NIU (发电技术)
The construction of ubiquitous power internet of things (UPIoT) is mainly to apply new technologies and ideas such as information technology and artificial intelligence to the development process of enterprises in order to improve technological level of power enterprises. At the same time, it also serves the national strategic needs and conforms to the strategic requirements of promoting the deep integration of internet, big data, artificial intelligence and manufacturing industry. It is of great significance for promoting China's scientific and technological progress, industrial upgrading and improving people's living standards. The background, construction goals and significance of UPIoT was Introduced. Technical support of UPIoT construction was analyzed. The attitudes and corresponding measures of some communities towards UPIoT was discussed. The typical application of UPIoT at present was illustrated, and finally the possible problems in the development process of UPIoT were analyzed.